Elevated prevalence and treatment of sleep disorders from 2011 to 2020: a nationwide population-based retrospective cohort study in Korea - Younghwa Baek; Siwoo Lee; Ji-Eun Park; Eunkyoung Ahn; Hee-Jeong Jin (BMJ Open, 2024)
Objectives This study used National Health Insurance claims data from Korea to report the prevalence of sleep disorders and treatment status, including traditional Korean medicine, in the last 10 years.Methods This is a retrospective cohort study in Korea. All diagnosis and prescription data, including herbal medicine claims, from the Health Insurance Review and Assessment Service from 2011 to 2020 were reviewed. Prevalence estimation, direct medical expenses and prescribed amounts for sleep disorders were recorded.Results The prevalence of sleep disorders increased from 3 867 975 (7.62%) in 2011 to 7 446 846 (14.41%) in 2020, nearly doubling over 10 years. Insomnia was observed in 91.44% (n=9 011 692) of the patients. The mean number of hospital visits per patient for sleep disorders was 11.5 (±26.62). Benzodiazepines are the most commonly prescribed medications for sleep disorders, and gamma-isoyosan is the most frequently prescribed herbal medicine.Conclusions Sleep disorders are continuously increasing, as is the use of medical services—personal and social medical expenses are also increasing accordingly. Sleep disorders should be recognised as a significant health problem that needs to be actively addressed to improve quality of life.